1998
DOI: 10.1117/12.331334
|View full text |Cite
|
Sign up to set email alerts
|

<title>Stray light design and analysis of the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) telescope</title>

Abstract: The Sounding of the Atmosphere using Broadband Emission Radiometiy (SABER) instrument is a 10-channel earth limbviewing sensor that is to measure atmospheric emissions in the spectral range of 1.27 jm to 16.9 iim. Presented in this paper is the stray light design and analysis of SABER Unwanted radiation from the eaith and atmosphere are suppressed by the use of stiay light features that are Critical to mission success. These include the use ofan intermediate field stop, an inner and outer Lyot stop, and super-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The stray light analysis program APART was used to predict SABER's off-axis response and to aid in the telescope design 5,6 . The software model showed that mirror scatter is the dominant source of stray light for the short wavelength channels.…”
Section: Comparison Of Measured Results To Software Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The stray light analysis program APART was used to predict SABER's off-axis response and to aid in the telescope design 5,6 . The software model showed that mirror scatter is the dominant source of stray light for the short wavelength channels.…”
Section: Comparison Of Measured Results To Software Modelmentioning
confidence: 99%
“…The instrument description and mission objectives are described in greater detail elsewhere 1,2 . Stray light analyses performed using the software programs APART 3 and ASAP 4 have also been documented [5][6][7] . The results of the off-axis response measurement of SABER are presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 High off-axis rejection performance was obtained by extensive straylight analyses and optimization during design and the required use of nearly pristine, superpolished fore-optics. 3,4 Furthermore, an intermediate field stop and an inner Lyot stop are incorporated to eliminate the stray light and diffraction effects that are typically associated with on-axis telescope designs. 5 The scan mirror has approximately 100° range of motion that allows it to scan across the entrance aperture or rotate to a position for on-orbit calibration using the inflight calibrator (IFC) blackbody.…”
Section: Generalmentioning
confidence: 99%
“…Radiation blocking scheme might also produce a great amount of reflected and absorbed radiation that travels all over and causes stray-light noise (Scholl, 1994b;Stauder & Esplin, 1998) and heating. Such scattered radiation might easily drown the faint signal (Scholl, 1996b).…”
Section: Coronagraphic Estrella Signal Eliminationmentioning
confidence: 99%